A Study to Assess the Effectiveness of Lemon Juice in Improving Hemoglobin Level Among Adolescent Girls in Selected Schools of Jabalpur City - Sahu, Rashmi (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The study aimed to access the effectiveness of the lemon juice in improving hemoglobin level among adolescent girls. Material and Methods: Quasi-experimental pre- and post-test only control group design two group control group and experimental group design was carried out in selected schools with similar setting in Jabalpur city. Purposive sampling technique was used for the study. Sample study for this study was 120 adolescent girls in the total of those 60 were selected for experimental group 30 and 30 in the control group. The experimental groups were given lemon juice whereas the control groups were not given any intervention. Results: The comparison between pre- and post-score was statistically tested by applying t-test method at the level of 0.05%. In this case, the calculated value of paired t-test = 0.657463 is less than the table value (“t” 29=2.05, P < 0.05); hence, the result was insignificant. The comparison between experimental group and control group hemoglobin score made by unpaired t-test is 8.56 (“t” 29=1.699, P < 0.05) greater than the table value. It shows that lemon juice administration for 1 month is increasing hemoglobin in adolescent girls. Conclusion: From the study findings, it is concluded that there are significant differences on the adolescent girls before and after administration of lemon juice. The present study also proved that there was a significant difference on the increase hemoglobin level between experimental and control group. Hence, it may be stated that the lemon juice has an effect on increasing hemoglobin level among adolescent girls.